Subconscious visual cues during movement execution allow correct online choice reactions. - Christian Leukel; Jesper Lundbye-Jensen; Mark Schram Christensen; Albert Gollhofer; Jens Bo Nielsen; Wolfgang Taube (PLoS ONE, 2012)
Part of the sensory information is processed by our central nervous system without conscious perception. Subconscious processing has been shown to be capable of triggering motor reactions. In the present study, we asked the question whether visual information, which is not consciously perceived, could influence decision-making in a choice reaction task. Ten healthy subjects (28 ± 5 years) executed two different experimental protocols. In the Motor reaction protocol, a visual target cue was shown on a computer screen. Depending on the displayed cue, subjects had to either complete a reaching movement (go-condition) or had to abort the movement (stop-condition). The cue was presented with different display durations (20-160 ms). In the second Verbalization protocol, subjects verbalized what they experienced on the screen. Again, the cue was presented with different display durations. This second protocol tested for conscious perception of the visual cue. The results of this study show that subjects achieved significantly more correct responses in the Motor reaction protocol than in the Verbalization protocol. This difference was only observed at the very short display durations of the visual cue. Since correct responses in the Verbalization protocol required conscious perception of the visual information, our findings imply that the subjects performed correct motor responses to visual cues, which they were not conscious about. It is therefore concluded that humans may reach decisions based on subconscious visual information in a choice reaction task.